Gospel Interpretation and the Q-Hypothesis. - Keith, Chris (The Library of New Testament Studies, 2018)
Cover -- Series -- Title -- Copyright -- Contents -- Preface -- List of Contributors -- Chapter 1 Introduction: What is at Stake by Advocating or Disputing the Two-Source Theory? -- Part I History and Theory -- Chapter 2 Conceptual Stakes in the Synoptic Problem -- 2.1 Methodological Issues -- 2.1.1 The Primary Data for the Synoptic Problem -- 2.1.2 Data, Inference and Editorial Scenarios -- 2.1.2.1 Describing the Data -- 2.1.2.2 Logical Inferences -- 2.1.2.3 Editorial Scenarios -- 2.2 Towards a Critical History of the Synoptic Problem -- 2.2.1 The Synoptic Problem and the Historical Jesus -- 2.2.2 The Conceptual Landscape of the Early Jesus Movement -- 2.2.3 Why Might This Matter? -- Chapter 3 Sad Sources: Observations from the History of Theology on the Origins and Contours of the Synoptic Problem -- 3.1 The Witness of the Gospels: Difference and Harmony from Luke to Augustine -- 3.1.1 From the Gospel to the Gospels -- 3.1.2 Legends about the Four Evangelists in the Early Church -- 3.1.3 Strategies to Counteract Confusion That Might be Caused by the Polyphony of the Gospels -- 3.1.3.1 Luke, Marcion and Tatian -- 3.1.3.2 Origen vs. Celsus -- 3.1.3.3 Augustine vs. Porphyry -- 3.2. From the Perspicuity (Klarheit) of Scripture to the Synoptic Problem -- 3.2.1 From Gospel Harmonies to the Perspicuity of Scripture -- 3.2.2 Ad Fontes -- 3.3 The Significance of the Wars of Religion for the Development of Christian Biblical Criticism -- 3.3.1 From the Perspicuity of Scripture to Clarity of Analysis -- 3.3.2 Disharmonization Strategies: Semler and Reimarus -- 3.3.3 Strategies of Reharmonization: The Griesbach Hypothesis and Eichhornâs âUr-Gospelâ Hypothesis -- 3.3.3.1 The Griesbach Hypothesis -- 3.3.3.2 The âUr-Gospelâ Hypothesis of Johann Gottfried Eichhorn -- 3.4 Afraid of the Myth: How the Two-Source Hypothesis Came into Being